DIABETIC WOUND MANAGEMENT: FROM PATHOPHYSIOLOGY TO CLINICAL PRACTICE (CIPEEX, 2025)
Introduction Diabetes Mellitus is a chronic disease with a high global prevalence that poses a significant challenge to public health, especially concerning its complications. In this context, compromised wound healing is one of the most serious complications, directly linked to persistent hyperglycemia and metabolic dysfunctions that affect hemostasis, inflammation, angiogenesis, and tissue regeneration. In diabetic foot, lesions are a recurrent problem, often evolving into chronic ulcers primarily due to diabetic neuropathy and the resulting loss of sensation. Given this scenario, it's crucial to understand the complex process of tissue repair in diabetic patients to guide clinical management and treatment strategies effectively. Objective To highlight the importance of knowledge about the process of diabetic wound healing and, consequently, the type of clinical management to be used in a diabetic patient. Methods This is an integrative literature review conducted through searches in the PubMed, SciELO, and Google Scholar databases. Only full-text articles that were freely available, in Portuguese or English, were included. The descriptors used were "Wound Healing," "Diabetes Mellitus," and "Diabetic Foot." Publications that did not meet these criteria or did not correspond to the central objective were excluded. Results Wound management in diabetic patients requires a more complex approach than simple local treatment. This is because compromised wound healing in DM is not an isolated phenomenon; it's exacerbated by the presence of infections, which can range from superficial (caused by Staphylococcus aureus) to deep polymicrobial infections involving enterobacteria, Pseudomonas, and anaerobes. This microbiological complexity demands a detailed clinical evaluation, including laboratory tests and cultures, to guide appropriate antibiotic therapy. Furthermore, treatment must be multidisciplinary, incorporating specialized dressings, skin hydration, debridement of necrotic tissue, and, in severe cases, surgical intervention. The presence of comorbidities like peripheral arterial occlusive disease and acute kidney failure further worsens the prognosis, making healing a slow and challenging process. Prevention, therefore, emerges as a fundamental pillar, encompassing strict glycemic control, regular physical activity, a balanced diet, and specific foot care, such as the selection of appropriate footwear and baropodometry. Conclusion The process of wound healing in patients with Diabetes Mellitus is intrinsically complex and requires a deep understanding of the underlying pathophysiological mechanisms. The complications, especially in the diabetic foot, demonstrate the need for comprehensive and multidisciplinary management. By integrating metabolic control, targeted treatment of infections, and preventive care, it's possible to reduce the risk of serious complications like amputations. Thus, by aligning healthcare professionals' knowledge of diabetic wound healing, one can optimize healing, minimize complications, and improve patients' quality of life.
Keywords: Diabete Mellitus; Wound Healing; Diabetic Foot